The Making of an Organic Waste Shredding Machine to Improve Agricultural Yields in Pasir Impun Village - Nugraha, Noviyanti; Hadiatna, Febrian; ramadhan, Rayi Kesuma; Franciscus, Hariyogi; Rachman, Randi M.; Dziqy, Alif Daffa; Spriadi, Affandi (Institut Teknologi Nasional, Bandung, 2025)
Compost fertilizer is a type of fertilizer used by the Nur Alam community to enrich their agricultural land. This fertilizer is needed in large quantities every week. In this community service activity, a composting machine was created to assist Nur Alam Tani with their fertilizer needs. The function of this machine is to accelerate the compost production process by shredding waste into smaller sizes. The machine has dimensions of 490 x 455 x 950 mm. An electric motor with a power specification of 1Hp is used as its drive. This machine is capable of processing waste at a rate of 5 kg/hour, producing shredded material with an approximate size of 10 mm. The output from this machine has greatly benefited Nur Alam Tani, as prior to the use of this device, they were only able to produce about 10 kg of fertilizer per week.